Effects of Ascophyllum nodosum seaweed extracts on lettuce growth, physiology and fresh-cut salad storage under potassium deficiency - Chrysargyris, Antonios; Xylia, Panayiota; Anastasiou, Myria; Pantelides, Iakovos S; Tzortzakis, Nikos G. (My University, 2018)
BACKGROUND: Potassium (K) deficiency in leafy vegetables such as lettuce is a major concern regarding quality. Seaweed (SW) extracts, as biostimulants, are biodegradable materials and have become increasingly popular as they are reported to enhance crop growth and yield. RESULTS: In order to overcome K deficiencies (i.e. 375 vs 125 mg L−1), alternative foliar applications with extracts of Ascophyllum nodosum SW or K were examined using lettuce plants which were grown hydroponically. Potassium deficiency (at 125 mg L−1) reduced plant biomass, photosynthetic rate, leaf stomatal conductance, lettuce potassium content and tissue antioxidant capacity as compared with the higher K level (375 mg L−1). Application of SW increased the relative growth of lettuce in the low-K treatment. The K level and/or SW application altered the plant's enzyme protective activity (superoxide dismutase, SOD; catalase, CAT; peroxidase, POD) against oxidative stress and hydrogen peroxide (H2O2) production. Spray applications of SW mitigated the effects of K deficiency on indicators of enzyme activity and plant damage, back to levels of high K content (375 mg L−1). The high K level, but also SW application, increased the antioxidant activity of the processed lettuce before storage. Foliar application of the SW extract increased the quality of cut lettuce grown in 125 mg L−1 K conditions by reducing the rate of respiration and increasing consumer preference. CONCLUSION: The SW application could alter the detrimental effects of K deficiency during lettuce growth and storage of processed products. © 2018 Society of Chemical Industry.
Keywords: Antioxidant capacity; Biostimulants; Fresh-cut salads; Lettuce; Seaweed; Shelf life